DEMOKRASI DIGITAL: TANTANGAN DAN PELUANG DALAM ERA MEDIA SOSIAL - Sapitra, Chalizah (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2024)
The development of information and communication technology has driven a major transformation in democratic practices, especially through social media. Digital democracy creates new spaces for public participation, government transparency, and faster, broader information dissemination. However, the social media era also brings serious challenges such as disinformation, hate speech, and public opinion polarization. This study aims to examine the dynamics of digital democracy by highlighting the opportunities and challenges that arise in the context of social media use as a political medium. Using a qualitative approach and literature review, it is found that although social media can enhance political participation, strong regulation and digital literacy are essential to maintain the quality of democracy itself.